The Quality of Education: a reflection from the Pedagogical Academic Management (2020)
The objective of the research is to recognize the impact of the academic and pedagogical management of the educational establishments of Santa Rosa de Osos municipality on the quality of education and which results will provide expertise to enable, facilitate, and improve the pedagogical and teachinglearning process. The paradigm is historical-hermeneutic of qualitative type and as a research strategy the case of study was privileged. In this order of ideas, it is intended to relate academic and pedagogical process with the quality of the educational institutions studied. Based on this, it is hoped that results will serve, in the immediate future, to be used in the reformulation of the projects, policies, and programs that seek to improve the quality of education